THE SEMICONDUCTOR REVOLUTION: ENABLING DIGITAL TRANSFORMATION IN DEVELOPING ECONOMIES - Sharvani Mukkala, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines the transformative impact of semiconductor technology on digital transformation in developing economies, focusing on its role in enabling affordable access to essential services. It analyzes how semiconductor advancements have facilitated the widespread adoption of mobile technologies across Africa, Southeast Asia, and Latin America, fundamentally changing how populations access financial services, healthcare, and education. The article highlights the crucial role of affordable semiconductor components in democratizing digital access, particularly through mobile devices and internet connectivity. Special attention is given to the acceleration of digital adoption during the COVID-19 pandemic, especially in educational contexts. The article explores how semiconductor-powered devices have enabled remote learning solutions, telemedicine services, and mobile payment systems in resource-constrained environments. Furthermore, it investigates the future implications of semiconductor technology in developing regions, examining emerging trends in 5G adoption, artificial intelligence processing capabilities, and Internet of Things applications, while considering the challenges and opportunities in local semiconductor manufacturing and assembly.